Cigarette smoking, comorbidity, and general health among survivors of adolescent and young adult cancer. Issue 18 (10th June 2016) - Kaul, Sapna; Veeranki, Sreenivas P.; Rodriguez, Ana M.; Kuo, Yong‐Fang
Abstract : BACKGROUND: We examined the associations between cigarette smoking, comorbidity, and general health among survivors of adolescent and young adult (AYA) cancer and a comparison group. METHODS: From the 2012 to 2014 National Health Interview Surveys, we identified 1019 survivors of AYA cancer, defined as individuals who had been diagnosed with cancer between 15 and 39 years of age and were at least 5 years after their initial cancer diagnosis. A noncancer comparison group was matched on age, sex, and other factors. Self‐reported smoking status (never smoker, former smoker, or current smoker), comorbidities (eg, asthma and diabetes), and general health status (excellent, very good, or good versus poor or fair) were compared among these groups. Survivors' smoking status before diagnosis and interaction with health care professionals regarding smoking cessation were reported. Multivariable logistic regressions modeled the associations between smoking status and comorbidity and general health. RESULTS: 33% of survivors were current smokers compared with 22% in the comparison group ( P < .001). Prevalence of comorbidities and fair/poor health was significantly higher among survivors. Current smokers among survivors were more likely to report greater comorbidities (odds ratio [OR], 1.62; 95% confidence interval [CI], 1.06‐2.47; P = .03) and less likely to report at least good health (OR, 0.34; 95% CI, 0.22‐0.54; P < .001) than never‐smokers. Among survivors who smoked currently, 92% started smoking before diagnosis, and 37% reported having no smoking‐related discussions with health care professionals in the previous year. CONCLUSIONS: Smoking among survivors of AYA cancer is associated with greater comorbidities and poorer general health. Younger survivors may need to be targeted for effective smoking cessation interventions. Addressing cigarette smoking during medical visits may encourage survivors to quit smoking. Cancer 2016 . © 2016 American Cancer Society . Cancer 2016;122:2895–2905. © 2016 American Cancer Society Abstract : Survivors of adolescent and young adult cancer are more likely to smoke cigarettes than a comparison group. Cigarette smoking among survivors is associated with comorbidity and poor or fair general health. The majority of survivors start smoking before diagnosis, and nearly 40% of current smokers report not having smoking‐related discussions with health professionals in the previous year.